Evaluating the sensitivity of Centiloid quantification to pipeline design and image resoloution. (20th December 2022) - Shekari, Mahnaz; García, David Vállez; Collij, Lyduine E.; Heeman, Fiona; Roé‐Vellvé, Núria; Bullich, Santiago; Buckley, Christopher; Barkhof, Frederik; Farrar, Gill; Pemberton, Hugh; Gispert, Juan Domingo; ,
Abstract: Background: Wider use of amyloid PET in clinical routine requires validated and standardized quantification methods. Therefore, the impact of pipeline design and post‐processing smoothing on Centiloid(CL) quantification was evaluated. Method: This study has been performed using 725 amyloid PET scans from the two AMYPAD trials(PNHS and DPMS) that were acquired with either [ 18 F]flutemetamol or [ 18 F]florbetaben(Table1 ). Using SPM12, 32 pipelines were created and calibrated to render CL with combinations of: 4 reference regions (Whole Cerebellum, Cerebellar Gray, Whole Cerebellums+Brainstem, Pons) 2 target VOI (standard GAAIN vs subject‐based) 2 reference region type (standard GAAIN vs subject‐based) 2 analysis spaces (native vs MNI) The impact of the pipeline design factors on CL values assessed using Generalized Estimating Equation(GEE) analyses. Individual morphometric variables including total intracranial volume(TIV), and grey/white matter volumes in the reference and target regions implemented in the model. To mimic differences in image resolution, PET scans were smoothed by 3mm and 6mm Gaussian filters. CL was calculated for original and corresponding smoothed PET scans. The agreement between CL values with/without smoothing evaluated using the intra‐class correlation coefficient(ICC). Bland‐Altman plots were used to demonstrate mean absolute differences between CL values after smoothing. Differences above 5CL were considered relevant. Result: There was no statistically significant relationship for CL as a function of tracer, analysis space or target region, while RR selection and its definition did have a significant impact on CL values(Table2 ). More specifically, the pons provided the lowest mean CL(25.06±4.51 ) compared to the whole‐cerebellum(35.04±4.25 ) and the cerebellum grey‐matter(36.99±4.16 )(Table3 ). Using GAAIN RR provided slightly higher mean CL values (ΔCL 4.15±1.04 ) compared to a subject‐based method (Table4 ). ICC between CL values of non‐smoothed vs smoothed PET images was 0.99 for both post‐smoothing filters(p<0.001 ). Differences in image resolution had minimal effect on CL values for individuals with low to moderate levels of amyloid while the effect became higher for individuals with the higher amyloid burden(Figure1) Conclusion: CL quantification is robust against differences in individual morphometric measures, analysis space, image resolution, tracer and target VOI. However, reference region choice can significantly influence CL values, with the pons showing the highest discrepancies relative to other reference regions.